Survival and metabolic characteristics of Lux-Marked Escherichia coli O157:H7 in different types of milk - Lahmer, Rabya A.; Jones, Davey L.; Williams, Prysor (Al-Mukhtar Journal of Sciences, 2016)
Escherichia coli O157:H7 is a potentially lethal pathogen which has been responsible for several outbreaks of milk-borne illness in recent years. The objective of this study was to evaluate the survival and metabolic activity (indexed by bioluminescence) of a chromosomally lux-marked strain of E. coli O157:H7 in raw, pasteurized and microfiltered pasteurized milk at 4 and 20°C for up to 14 d. Results showed that the population of E. coli O157:H7 and its metabolic activity decreased in all samples during storage at 4°C, with no significant differences in numbers observed between the different milk types; but the metabolic activity was significantly higher (P<0.05) in the microfiltered pasteurized milk than that in raw milk. At 20°C, E. coli O157:H7 counts and cell activity peaked at day 2, and then declined progressively. At 20°C, survival and metabolic activity were significantly lower in raw milk compared with pasteurized milk. We conclude that storage temperature is more important in regulating the survival of E. coli O157:H7 in contaminated milk than its origin/pre–treatment conditions.